Peningkatan Kedisiplinan dengan Konseling Kelompok Melalui Teknik Token Economy Bagi Peserta Didik SMPN 3 Banyuates - Titie Nurhayati (Nusantara of Research : Jurnal Hasil-hasil Penelitian Universitas Nusantara PGRI Kediri, 2020)
Discipline attitude is an important and main aspect of education, so it is hoped that students can control their behavior in accordance with applicable norms. In connection with this mission, it is felt the need for effective and efficient guidance and counseling services to help overcome the problems that are being faced by students. The guidance and counseling teachers considered the use of information services to be less than optimal, so this time using group counseling services. The purpose of this research is to improve the disciplinary behavior of students. There are many treatments that can be done to improve discipline, one of which is behavior modification therapy. What will be used in behavior modification is to use the token economy technique, namely by providing positive reinforcement. This guidance and counseling action research uses classroom action research. Purposive sampling technique was used in this guidance and counseling action research. Based on the results of observations made during the study, there was a significant change in disciplinary behavior from the act of giving the token economy in cycle 1 and cycle 2.